A Multilocus Approach to Understanding Historical and Contemporary Demography of the Keystone Floodplain Species Colossoma macropomum (Teleostei: Characiformes) - Santos, Maria da Conceição Freitas; Hrbek, Tomas; Farias, Izeni P. (Frontiers in Genetics, 2018)
We study the natural populations of a symbol fish of the Amazon, the Colossoma macropomum which in recent years has been suffering from severe exploitation. Our aim was to investigate the existence or not of genetic differentiation covering a wide area of its distribution and to investigate changes in its effective population size throughout its evolutionary history. We sampled individuals from 21 locations distributed throughout the Amazon basin. We analyzed 539 individuals for mitochondrial genes (control region and ATPase gene 6/8), generating 1561 base pairs, and genotyped 604 individuals for 13 microsatellite loci obtaining, on average, 21.4 alleles per locus. Mean HE was 0.78 at all sampling sites suggesting moderate levels of genetic variability among fish populations. AMOVA and other tests used to detect the population structure based on both markers indicate that C. macropomum comprises a single and large panmitic population in the main channel of the Solimões-Amazonas river basin, on the other hand localities in the headwaters of the tributaries Juruá, Purus, Madeira, Tapajós and localities of black water, showed genetic structure. The greatest genetic differentiation was observed between the Brazilian Amazon basin and the Bolivian sub-basin with a restricted genetic flow between the two basins. Demographic analyzes of mitochondrial genes indicated population expansion in the Brazilian and Bolivian Amazon basins during the Pleistocene, and microsatellite data indicated a reduction in population during the Holocene. This shows that the historical demography of C. macropomum is highly dynamic. Conservation and management strategies should be designed to respect the existing population structure and minimize the effects of the composition of the current overfishing by limiting fisheries on C. macropomum populations from the headland sites of the tributaries sampled in this study.